Frame contention in different types of media ownership - a comparison between the star online and sinar online’s media coverage on 2017 budget / Mohammad Noorhusni Mohd Zaini and Abd Rasid Abd Rahman - Mohd Zaini, Mohammad Noorhusni; Abd Rahman, Abd Rasid (Centre for Media and Information Warfare Studies, 2017)
This study intends to examine the difference of media coverage between The Star, owned by ruling party and Sinar Harian, a privately-owned news provider on the 2017 Budget. Media ownership is understood to be affecting objectivity in media coverage, given its influence on the sources to be used, as well as how issues are portrayed. This content analysis study used a census sample of the first 14 days after its tabling. To differentiate the coverage between these two mainstream news provider, the researcher studied the sources used by both news providers, frames utilized in the coverage of the budget using Semetko and Valkenberg’s (2000) generic news frame, as well as the news slants that are apparent in both news providers’ reporting of the budget as basis for comparison. Results of the study show that while both news providers mostly used the ruling government representative as their sources and the responsibility frame in their coverage, a sheer difference can be seen in the news slants as The Star’s coverage of the budget are more positive, as compared to Sinar Online which can be considered more balanced. Nevertheless, Sinar Online was found to have tendencies to politicize its coverage of the budget; by employing more conflict frames on issues not directly related to the content of the budget, as well as using more opposition party members as their news sources.